Colonic EBV-Associated Lymphoproliferative Disorder in a Patient Treated with Rabbit Antithymocyte Globulin for Aplastic Anemia - Hiroko Sugimoto-Sekiguchi; Haruko Tashiro; Ryosuke Shirasaki; Tomio Arai; Tadashi Yamamoto; Yoko Oka; Nobu Akiyama; Kazuo Kawasugi; Naoki Shirafuji (Case Reports in Gastrointestinal Medicine)
Epstein-Barr-virus- (EBV-) associated lymphoproliferative disorder (LPD) after immunosuppressive therapy for aplastic anemia (AA), in a nontransplant setting, has not been well described. We report one case of colonic EBV-LPD after a single course of immunosuppressive therapy for AA. The patient developed multiple colonic tumors 3 months after receiving immunosuppressive therapy, which consisted of rabbit antithymocyte globulin (ATG), cyclosporine, and methyl-predonisolone. The histological findings of biopsy specimens revealed that atypical lymphocytes had infiltrated colonic glands. Immunohistochemical staining for CD20 was positive, and in situ hybridization for EBV-encoded small RNAs was also positive. The EBV viral load in peripheral blood was slightly increased to 140/106 white blood cells. After the cessation of immunosuppressant, the colonic tumors spontaneously regressed, and the EBV viral load decreased to undetectable levels. This is the first report of the single use of rabbit ATG inducing colonic EBV-LPD. Because a single use of immunosuppressive therapy containing rabbit ATG can cause EBV-LPD, we should carefully observe patients receiving rabbit ATG for AA.